2009
DOI: 10.1007/s11241-009-9071-z
|View full text |Cite
|
Sign up to set email alerts
|

Worst-case response time analysis of real-time tasks under fixed-priority scheduling with deferred preemption

Abstract: Fixed-priority scheduling with deferred preemption (FPDS) has been proposed in the literature as a viable alternative to fixed-priority pre-emptive scheduling (FPPS), that obviates the need for non-trivial resource access protocols and reduces the cost of arbitrary preemptions. This paper shows that existing worst-case response time analysis of hard real-time tasks under FPDS, arbitrary phasing and relative deadlines at most equal to periods is pessimistic and/or optimistic. The same problem also arises for fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 29 publications
(53 reference statements)
0
101
0
Order By: Relevance
“…Subsequent research by Bril et al (2009) has refined exact analysis of FP-NP, correcting issues of both pessimism and optimism, and extending the schedulability tests to co-operative scheduling where each task is made up of a number of non-pre-emptive regions.…”
Section: Resource Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent research by Bril et al (2009) has refined exact analysis of FP-NP, correcting issues of both pessimism and optimism, and extending the schedulability tests to co-operative scheduling where each task is made up of a number of non-pre-emptive regions.…”
Section: Resource Sharingmentioning
confidence: 99%
“…Further, the minimum possible amount of time 8 ∆ prior to this simultaneous release, a lower priority task k  is released, and this task has the longest execution time of any such lower priority task. George et al (1996) and Bril et al (2009) showed that for fixed priority non-pre-emptive scheduling, the longest response time of a task i  occurs for some job of that task within the priority level-i busy period starting at a ∆-critical instant. Lemma 3 in (Bril et al 2009) states that the worstcase length of a priority level-i busy period i A is given by the minimum solution to the following fixed point iteration:…”
Section: Schedulability Analysis For Fp-npmentioning
confidence: 99%
“…In general, all jobs in the busy-period at the task's priority level need to be checked to see which gives the largest response time. The analysis used by Davis and Bertogna [15] follows the approach introduced by Bril [10], [11].…”
Section: B Deferred Preemptionmentioning
confidence: 99%
“…(2)) with the framework given by the series of equations (5) to (11). Hence, for the LO-criticality mode, (7) becomes:…”
Section: B Schedulability Analysis For Amc-nprmentioning
confidence: 99%
“…Saksena and Wang 2000;Wang and Saksena 1999); (2) executing certain parts of a task in a nonpreemptive manner (e.g. Bril et al 2009;Bertogna et al 2011a, b;Davis and Bertogna 2012); (3) a combination of the two former approaches (e.g. Bril et al 2012).…”
Section: Related Workmentioning
confidence: 99%